PlaToLoCo: the first web meta-server for visualization and annotation of low complexity regions in proteins. Issue Volume 48:Issue W1(2020) (18th May 2020) - Jarnot, Patryk; Ziemska-Legiecka, Joanna; Dobson, Laszlo; Merski, Matthew; Mier, Pablo; Andrade-Navarro, Miguel A; Hancock, John M; Dosztányi, Zsuzsanna; Paladin, Lisanna; Necci, Marco; Piovesan, Damiano; Tosatto, Silvio C E; et al.
Abstract: Low complexity regions (LCRs) in protein sequences are characterized by a less diverse amino acid composition compared to typically observed sequence diversity. Recent studies have shown that LCRs may co-occur with intrinsically disordered regions, are highly conserved in many organisms, and often play important roles in protein functions and in diseases. In previous decades, several methods have been developed to identify regions with LCRs or amino acid bias, but most of them as stand-alone applications and currently there is no web-based tool which allows users to explore LCRs in protein sequences with additional functional annotations. We aim to fill this gap by providing PlaToLoCo - PLAtform of TOols for LOw COmplexity—a meta-server that integrates and collects the output of five different state-of-the-art tools for discovering LCRs and provides functional annotations such as domain detection, transmembrane segment prediction, and calculation of amino acid frequencies. In addition, the union or intersection of the results of the search on a query sequence can be obtained. By developing the PlaToLoCo meta-server, we provide the community with a fast and easily accessible tool for the analysis of LCRs with additional information included to aid the interpretation of the results. The PlaToLoCo platform is available at: http://platoloco.aei.polsl.pl/ . Graphical Abstract: